Ergosterol peroxide from Chaga mushroom (Inonotus obliquus) exhibits anti-cancer activity by down-regulation of the β-catenin pathway in colorectal cancer. (15th September 2015) - Kang, Ju-Hee; Jang, Jeong-Eun; Mishra, Siddhartha Kumar; Lee, Hee-Ju; Nho, Chu Won; Shin, Dongyun; Jin, Mirim; Kim, Mi Kyung; Choi, Changsun; Oh, Seung Hyun
Abstract: Aim of the study: In this study, we examined the effect of different fractions and components of Chaga mushroom (Inonotus Obliquus) on viability and apoptosis of colon cancer cells. Among them, one component showed the most effective growth inhibition and was identified as ergosterol peroxide by NMR analysis. We investigated the anti-proliferative and apoptosis mechanisms of ergosterol peroxide associated with its anti-cancer activities in human colorectal cancer (CRC) cell lines and tested its anti-tumor effect on colitis-induced CRC developed by Azoxymethane (AOM)/Dextran sulfate sodium (DSS) in a mouse model. Materials and methods: We used MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) assays, flow cytometry assays, Western blot analysis, colony formation assays, reverse transcription-polymerase chain reaction (RT-PCR), immunohistochemistry (IHC), and AOM/DSS mouse models to study the molecular mechanism of metastatic activities in CRC cells. Results: Ergosterol peroxide inhibited cell proliferation and also suppressed clonogenic colony formation in HCT116, HT-29, SW620 and DLD-1 CRC cell lines. The growth inhibition observed in these CRC cell lines was the result of apoptosis, which was confirmed by FACS analysis and Western blotting. Ergosterol peroxide inhibited the nuclear levels of β-catenin, which ultimately resulted in reduced transcription of c-Myc, cyclin D1, and CDK-8. Ergosterol peroxide administration showed a tendency to suppress tumor growth in the colon of AOM/DSS-treated mice, and quantification of the IHC staining showed a dramatic decrease in the Ki67-positive staining and an increase in the TUNEL staining of colonic epithelial cells in AOM/DSS-treated mice by ergosterol peroxide for both prevention and therapy. Conclusion: Our data suggest that ergosterol peroxide suppresses the proliferation of CRC cell lines and effectively inhibits colitis-associated colon cancer in AOM/DSS-treated mice. Ergosterol peroxide down-regulated β-catenin signaling, which exerted anti-proliferative and pro-apoptotic activities in CRC cells. These properties of ergosterol peroxide advocate its use as a supplement in colon cancer chemoprevention. Graphical abstract: